Application of PT-84 polymer in HDD mud - lab research - Kowalczyk-Cudak, Danuta; Ropka, Anna; Wysocki, Sławomir (My University, 2011)
One of the most important in HDD technology is a drilling mud with specific properties. In this paper the results of PT-84 polymer application in HDD drilling mud are presented. Tested mud characterize with good technological properties, it gives good perspectives of industrial development.

W niniejszym artykule przedstawiono wyniki badań dotyczących aplikacji środka polimerowego PT-84 przeznaczonego do płuczek HDD. Przebadane płuczki charakteryzują się dobrymi parametrami technologicznymi, co pozwala na zastosowanie ich w praktyce przemysłowej.
Badania laboratoryjne nad zastosowaniem środka polimerowego PT-84 do płuczek HDD
Wiertnictwo, Nafta, Gaz
Keywords: drilling fluids; płuczki wiertnicze; horizontal directional drilling; wiercenia HDD